Internalization of Local Wisdom Values In Social Science Learning to Form Students' Character - Aris Aris; Apriyanda Kusuma Wijaya (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
The aim of this research is to explore the integration of local wisdom values in social studies learning towards the formation of student character. The subjects in this research are junior high school and MTs teachers in Kuningan Regency, then this research uses an exploratory descriptive qualitative method. Data collection techniques were carried out through observation and interviews. Next, data triangulation was carried out as part of the analysis of research results and to obtain the validity of the data obtained. From the research that has been carried out, the results show that there are several character values that are formed through the integration of local wisdom values in learning, namely religious, nationalist, disciplined, mutual cooperation characters. These several character values are then studied into five main character development values, namely religious character values, nationalist character values, independent character, mutual cooperation character and integrity character. The formation of these character values can be done by internalizing them in learning materials and habituation activity programs at school such as readhaton, regional fiction literacy, singing the national obligatory song, motivational programs, and environmental care activities.Keywords: Student Character, Local Wisdom, Social Studies Learning.